Incidencia de la disposición de los residuos sólidos del Área Agropecuaria en la calidad ambiental (estética) de la ESPAM “MFL” - Vera Vera, Deysi Verónica (2018)
The purpose of this study was to evaluate the incidence of the disposal of solid waste on the environmental quality (aesthetics) of the Agricultural Area of the MFL ESPAM. For this purpose, the solid waste management process was diagnosed through a field visit to the generation and intermediate collection points. Additionally, the officials in charge of the collection were visited, raising the relevant technical information on the problem. For the fulfillment of the objectives it was necessary to implement a survey to a universe population of 624 people and a sample size of 238 observations. The deficient disposal of solid waste was identified as the main incident factor, having as main aspects the deficient environmental training of the actors, inadequate frequency and collection schedule; location, quantity and type of containers for the disposal of common and hazardous waste; poor distribution system and mainly the poor distribution of containers for the intermediate disposal of solid waste. It was found that all the factors identified have a negative impact on the aesthetics of the agricultural area, which is why an Environmental Management Plan for the Efficient Management of Solid Waste was designed. This environmental management plan contains introduction, justification, objectives, strategic plan, operational plan, conclusions and recommendations, registering as a fundamental tool for the polluting mitigation of the bad management of solid waste and its incidence environmental quality (aesthetics) of the Agricultural Area of the MFL ESPAM.